In-House Training for Islamic Elementary School Teachers: Developing P5-PPRA Modules within the Merdeka Curriculum - Zulmasri Zulmasri; Wezi Arifnal; Rilvina Hildayati; Muhammad Idris (International Journal of Islamic Teaching and Learning, 2025)
The career of a teacher presents many challenges as well as rewards; without strong motivation, not everyone will be interested in this profession. This study aims to analyze and improve the quality of services to students in Islamic elementary schools through In-House Training activities, with a focus on implementing the Merdeka Curriculum and enhancing the knowledge and competence of teachers in compiling simple P5-PPRA modules. This study employed a qualitative method with a case study design. Data collection techniques included documentation, interviews, and observation. Data were obtained from twenty-six informants through in-depth interviews, selected using purposive sampling; all informants were active teachers in their respective professions. The teachers’ ability and expertise in creating project modules which were initially very simple improved significantly. After the In-House Training was conducted in the Islamic elementary school, the benefits perceived by teachers included increased professionalism, discipline, and competitiveness through the application of the Merdeka Curriculum and the Gasing Method oriented toward digital learning.